2012
DOI: 10.1007/s10522-012-9400-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of ozone in ameliorating the age-related biochemical changes in male rat cerebral cortex

Abstract: Controlled ozone (O(3)) administration is known to promote oxidative preconditioning and, thus, may reverse chronic oxidative stress that accompanies aging. Therefore, the present work was undertaken to study the potential role of O(3) in ameliorating certain age-related biochemical changes represented by impaired activities of inner mitochondrial membrane enzymes, compromised energy production and increased oxidative burden in male rat cerebral cortex. Prophylactic administration of O(3)-O(2) mixture to 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…The most relevant metabolic effect is the marked increase of the CYT-c an hour after the end of the blood reinjection. This result is in accordance with studies regarding aging, in which it was shown that administration of 0/03 mix ameliorated the age-related cerebrocortical alterations, including the complex IV (CYT-c) activity (28).…”
Section: Discussionsupporting
confidence: 92%
“…The most relevant metabolic effect is the marked increase of the CYT-c an hour after the end of the blood reinjection. This result is in accordance with studies regarding aging, in which it was shown that administration of 0/03 mix ameliorated the age-related cerebrocortical alterations, including the complex IV (CYT-c) activity (28).…”
Section: Discussionsupporting
confidence: 92%
“…Most recently, ozone administered was reported to prevent atherosclerosis development and increase antioxidant systems in New Zealand white rabbits [13]. The antioxidative effects of ozone also ameliorate the age-related biochemical changes in male rat cerebral cortex [14]. In patients with coronary artery disease (CAD), ozone treatment by rectal insufflation significantly improved prothrombin time, reduced biomarkers of protein and lipid oxidation, and increased total antioxidant [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prophylactic administration of O 3 in aged-rats normalized reduced GSH content, adenosine triphosphate/adenosine diphosphate ratio, mitochondrial SOD and complex IV (cytochrome-c oxidase) activities. O 3 improved glutathione redox index (GSHRI), complex I (NADH-ubiquinone oxidoreductase) and mitochondrial mtNOS activities, and attenuated the rise MDA and mitochondrial PC levels ( Shehata et al, 2012 ).…”
Section: Pro-oxidation and Antioxidant Defence Biomarkers Influenced mentioning
confidence: 99%